Substantivity of Chlorhexidine to Human Dentin - Carrilho, Marcela R. (2010)
OBJECTIVES: To better comprehend the role of CHX in the preservation of resin-dentin bonds, this study investigated the substantivity of CHX to human dentin. MATERIAL AND METHODS: Dentin disks (n= 45) were obtained from the mid-coronal portion of human third molars. One-third of dentin disks were kept mineralized (MD), while the other two-thirds had one of the surfaces partially demineralized with 37% phosphoric acid for 15 s (PDD) or they were totally demineralized with 10% phosphoric acid (TDD). Disks of hydroxyapatite (HA) were also prepared. Specimens were treated with: 1) 10 μL of distilled water (controls), 2) 10 μL of 0.2% chlorhexidine diacetate (0.2% CHX) or 3) 10 μL of 2% chlorhexidine diacetate (2% CHX). Then, they were incubated in 1 mL of PBS (pH 7.4, 37 °C). Substantivity was evaluated as a function of the CHX-applied dose after: 0.5h, 1h, 3h, 6h, 24h, 168h (1wk), 672h (4wks) and 1344h (8wks) of incubation. CHX concentration in eluates was spectrophotometrically analyzed at 260 nm. RESULTS: Significant amounts of CHX remained retained in dentin substrates (MD, PPD or TDD), independent on the CHX-applied dose or time of incubation (p<0.05). High amounts of retained CHX onto HA were observed only for specimens treated with the highest concentration of CHX (2%) (p<0.05). CONCLUSION: The outstanding substantivity of CHX to dentin and its reported effect on the inhibition of dentinal proteases may explain why CHX can prolong the durability of resin-dentin bonds.